Development of Science in the Mughal Dynasty in India - Mungasiroh, Ulfiyani; Mawardi, Kholid (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Dynasties in Islamic history often show that many areas lived and developed under the leadership of a king. Thus in Islamic political life various monarchical governments are justified in part because there appears to be an heir to the throne. Of course, like countries, Islamic dynasties experienced several triumphs and experienced declines and even collapse after enjoying extraordinary fame. For example, the Mughal dynasty only lasted about 332 years before falling to the British. The type of research used is library research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. The development of science and technology during the Mughal dynasty in India did not enjoy the same prestige as previous Islamic dynasties, but the science and technology recorded in the history of the Mughal dynasty was quite advanced, this can be seen from the Mughal legacy. A dynasty arose. Regarding internal factors, such as the emergence of weak rulers, the occurrence of power struggles between royal successors, and weak control of power. External factors were rebellions everywhere and the expansion of British colonialism into India.The collapse of the Mughal dynasty in India was caused by two factors. The first is internal factors, such as the emergence of weak rulers, the occurrence of power struggles between royal descendants, and weak control of power. Both are external factors, such as the occurrence of rebellions everywhere and the colonization that was about to be carried out by the British to India.